2020
DOI: 10.3310/phr08110
|View full text |Cite
|
Sign up to set email alerts
|

Text messaging and financial incentives to encourage weight loss in men with obesity: the Game of Stones feasibility RCT

Abstract: Background In 2016, 26% of UK men were estimated to be obese. Systematic reviews suggest that few men engage in formal weight loss interventions that support weight reduction and improve health. Objective To co-produce, with patient and public involvement, an acceptable and feasible randomised controlled trial design to test a men-only weight management intervention. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 98 publications
(248 reference statements)
0
9
0
Order By: Relevance
“…Consultation methods undertaken to inform the intervention design process varied across studies, including focus groups, workshops, survey data, and various patient and public involvement activities. Of the nine studies that consulted men, four specifically reported engaging with lower socioeconomic groups 99–102 . In the cultural adaptation of the Healthy Dads Healthy Kids intervention for men and children from low‐income Hispanic communities in the United States, family members participated in focus groups, online surveys, and interviews with findings reviewed by stakeholder experts to inform the adaptation 101 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Consultation methods undertaken to inform the intervention design process varied across studies, including focus groups, workshops, survey data, and various patient and public involvement activities. Of the nine studies that consulted men, four specifically reported engaging with lower socioeconomic groups 99–102 . In the cultural adaptation of the Healthy Dads Healthy Kids intervention for men and children from low‐income Hispanic communities in the United States, family members participated in focus groups, online surveys, and interviews with findings reviewed by stakeholder experts to inform the adaptation 101 .…”
Section: Resultsmentioning
confidence: 99%
“…In the Healthy Dads Healthy Kids feasibility study in the UK, individual and focus group interviews with fathers and other family members from a range of ethnic, religious, and socioeconomic groups informed the cultural adaptation of the programs, with patient and public involvement also integrated throughout 99 . In the “Game of Stones” feasibility trial of a remotely delivered individual intervention in Scotland, a focus group with men from lower socioeconomic areas informed the recruitment strategies; with a large survey, and patient and public involvement activities undertaken to inform the intervention design and study processes 41,102 . Eleven (30.6%) trials did not report intervention tailoring for men or undertake stakeholder or target group consultations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations